2016
DOI: 10.1111/tla.12092
|View full text |Cite
|
Sign up to set email alerts
|

Is U.S. Influence Dwindling in Latin America? Citizens’ Perspectives

Abstract: Although the United States remains the most important external actor inLatin America in terms of investment, trade and foreign assistance, scholars and pundits have argued that the influence of the U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Baker and Cupery (2013) find evidence that trade, aid, migration, and remittances promote opinions of the United States in Latin America that are more positive. Other studies have shown that membership in the Alliance for the Peoples of Our America (ALBA) has a negative association with both trust in the US government (Azpuru and Boniface 2015) and perceptions of the degree of US influence in the region (Azpuru 2016). 12 In general, this literature has acknowledged that opinion of the United States varies widely across the region and is likely to be affected by country-level contextual factors.…”
Section: Beyond Perumentioning
confidence: 99%
See 1 more Smart Citation
“…Baker and Cupery (2013) find evidence that trade, aid, migration, and remittances promote opinions of the United States in Latin America that are more positive. Other studies have shown that membership in the Alliance for the Peoples of Our America (ALBA) has a negative association with both trust in the US government (Azpuru and Boniface 2015) and perceptions of the degree of US influence in the region (Azpuru 2016). 12 In general, this literature has acknowledged that opinion of the United States varies widely across the region and is likely to be affected by country-level contextual factors.…”
Section: Beyond Perumentioning
confidence: 99%
“…Additionally, our theory should travel because it is not dependent upon specific contextual factors, geography, a history of conflict, or even a particular baseline level of opinion toward the United States. We control for a number of individual-level demographic and attitudinal variables that have been found to influence views of the United States (Azpuru 2016). Silliman (2014) finds that individual experiences of cultural and economic interconnectedness with the United States-through remittances, trade, or shared ideology-corresponds with more trust in the United States as well.…”
Section: Beyond Perumentioning
confidence: 99%
“…However, several papers investigate the fastgrowing economic relationship between China and the Latin American continent, evaluating case studies in the natural resource industry (González-Vincente, 2013), trade relationships and bilateral ties (Domínguez et al, 2006) and policy challenges arising from increased Chinese presence (Wise an Quiliconi, 2007). Furthermore, public perception of Latin American citizens on rising Chinese involvement and resulting societal, ecological and cultural challenges attracted growing research attention (Azpuru, 2016;Armony & Velásquez, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ecuador's Golden Years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) The dollarization of Ecuador's economy proved to be a success when the financial and economic system recovered gradually in 2000 (Jácaume, 2004). This rebound can in large parts be attributed to a thorough political re-organisation, rising oil prices and strong support by multilateral institutions (Jácaume, 2004 (Krauss & Bradsher, 2015), and the expulsion of the American ambassador (Azpuru, 2016). In the same stroke, collaboration with multilateral institutions including the World Bank and the International Monetary Fund (IMF) was put on halt (Toussaint, 2007).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation